SURGICAL VS. NON-SURGICAL APPROACHES IN VAGINAL AGENESIS: A SYSTEMATIC REVIEW - Paramita, Alma Dhiani; Azwinda, Farah; Putri, Anastassya Yuniar Setyo; Kurniawati, Eighty Mardiyan (jfpublisher, 2024)
Introduction. Vaginal agenesis is the rudimentary or complete absence of vagina. The treatment of vaginal agenesis consists of various surgical and non-surgical techniques. This systematic review aims to describe the differences between surgical and non-surgical techniques of vaginal agenesis treatment in terms of vaginal length and sexual function. Method. Electronic databases such as PubMed, Science Direct, and SCOPUS were searched for articles published between 2018-2023. Literature restricted for women with vaginal agenesis who underwent surgical or non-surgical techniques was reviewed. Cross-sectional studies, observational studies, cohort studies, and retrospective studies were included in this study. Out of 190 articles, 8 articles were analyzed. All studies that reported total vaginal length and sexual function after treatment were conducted. Result & Analysis. The mean total vaginal length in the non-surgical technique was 7.23 cm and 8.88 cm in the surgical technique. Meanwhile, the level of sexual function, as measured using the Female Sexual Function Index (FSFI) score, showed a result of 24.40 in non- surgical techniques and 25.23 in surgical techniques. There is also one article with surgical techniques that assesses the level of sexual function objectively, resulting in sexual function within normal limits. Discussion. Total vaginal length in both techniques was normal but not on the FSFI scores. However, surgical techniques showed a slightly higher outcome Even so, non-surgical techniques are also a good treatment option considering the outcome are not much different compared to surgical techniques.